The Use of MQ6 and Microcontroller of ATMega 2360 as a Leaks Detection Device of Liquid Petrolum Gas (LPG)" - Noorly Evalina; Abdul Azis; Zulfikar Zulfikar (Budapest International Research in Exact Sciences (BirEx) Journal, 2020)
In essence, an explosion from LPG gas cylinders can be avoided if precautions are taken early, when gas leaks occur through cylinders, regulators, hoses or gas stoves. Along with the development of increasingly modern science and technology, a security system is developed by providing an Early Warning System. If this system detects a system leak, it will give a signal to the LCD or buzzer. A gas leak gives a signal to the sensor to work, MQ-6 and a 2360 microcontroller to work detecting a gas leak which is then read on the LCD screen, and in certain circumstances the buzzer will sound. And turn off the relay so that the inlet voltage to supply the solenoid gas valve is cut off, and the gas line is closed. The maximum distance that the gas sensor can detect in this paper is 18 cm, if the voltage on the sensor is greater than 2.33 volts, the LCD will give a signal of a gas leak and the buzzer will sound.